Problems of SMART CITY Programs and Projects Evaluation - HORVÁTH, Marek; DZUPKA, Peter (Journal of Environmental Management and Tourism, 2019)
Smart cities are one of the answers for an increasing share of the population living in urban areas. Smart approaches should help cities to manage the liveable environment in the cities in a sustainable way. To evaluate the development in this area – evaluation of smart city projects and programs the suitable evaluation methodologies are needed. For the moment there exists no common methodology for evaluation of smart city projects and programs.  The main aim of this article therefore is, to identify, from existing literature, the main problems of smart city programs and project evaluation and the most common methodologies used for evaluation.  The general problem of evaluation is in the heterogeneity of the current cities and the challenges they face nowadays. These challenges together with new possibilities connected with IT solutions (IOT, big data) are changing the way future cities will be operated. According to our short research in current literature, it seems to be not so big issue for project-level evaluation, but it is a real issue when considering the evaluation of the program. It is very difficult to identify the total impact of the smart city activities on the city and its citizens.